(2x-17)+1x+59=360

Simple and best practice solution for (2x-17)+1x+59=360 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-17)+1x+59=360 equation:


Simplifying
(2x + -17) + 1x + 59 = 360

Reorder the terms:
(-17 + 2x) + 1x + 59 = 360

Remove parenthesis around (-17 + 2x)
-17 + 2x + 1x + 59 = 360

Reorder the terms:
-17 + 59 + 2x + 1x = 360

Combine like terms: -17 + 59 = 42
42 + 2x + 1x = 360

Combine like terms: 2x + 1x = 3x
42 + 3x = 360

Solving
42 + 3x = 360

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-42' to each side of the equation.
42 + -42 + 3x = 360 + -42

Combine like terms: 42 + -42 = 0
0 + 3x = 360 + -42
3x = 360 + -42

Combine like terms: 360 + -42 = 318
3x = 318

Divide each side by '3'.
x = 106

Simplifying
x = 106

See similar equations:

| 4x+20=45-x | | x=18+-7(2) | | 2x-2=-8+3x | | 5(y-3)-3(y-2)=8 | | (3)/(8)x-(1)/(4)=2 | | 40-x=12x | | 48=4n/7+n | | -8(-3)(-3)= | | y=-4(18+-7y)+18 | | 4z-11-z+2=0 | | -2x(5x-8)=6x | | 8a+3=3 | | 9x-1=125 | | 1/8(5x+4)=3.4 | | (1)/(8)x=(1)/(2) | | (x-5)/(3*x)+(6/2*x+1)=0 | | (8x+9)(7x^2+9x+9)= | | (5)/(6)x=-15 | | 5t-t-7=3t-4 | | 3/4(-4y-8x+4z) | | 6(2q+1)=9q-12 | | (7x^2-8x-10)(x-9)= | | 5x=4x-3/4 | | 3/5*10x | | 8.4o-6.8=14.3+6.3o | | 5+4y=2y-13 | | 10m+16n=140 | | -2x^4y^2= | | -27x-9y=18 | | N^2+5n-266=0 | | 2(3x-2)-5x=5-2x | | X-(45)=16 |

Equations solver categories